Percolation Theory for Flow in Porous Media - Hunt, Allen G.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2005)
The present monograph presents, for the first time, a unified and comprehensive introduction to some of the basic transport properties of porous media, such as electrical and hydraulic conductivity, air permeability and diffusion. The treatment is based on critical path analysis and the scaling of transport properties which are individually described as functions of saturation. At the same time, the book supplies a tutorial on percolation theory for hydrologists, providing them with the tools for solving actual problems. In turn, a separate chapter serves to introduce physicists to some of the language and complications of groundwater hydrology necessary for succesful modelling.
Percolation Theory -- Porous Media Primer for Physicists -- Specific Examples of Critical Path Analysis -- Basic Constitutive Relations for Unsaturated Media -- Pressure Saturation Curves and the Critical Volume Fraction of Percolation -- Applications of the Correlation Length -- Applications of the Cluster Statistics -- Effects of Multi-Scale Heterogeneity.
Keywords: Earth sciences; Hydrology; Hydrogeology; Continuum physics; Statistical physics; Dynamical systems; Earth Sciences; Hydrogeology; Hydrology/Water Resources; Statistical Physics, Dynamical Systems and Complexity; Classical Continuum Physics; Earth Sciences, general; Electronic books